Rasa nyeri pada clear aligner : a scoping review - Lady Sekar Galih, Zefanya; Juliani, Magdalena (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: The prevalence of malocclusion in Indonesia reaches 80% of the Indonesian population. Removable orthodontic treatment using clear aligners is increasingly sought after due to its superior aesthetics and comfort relative to fixed orthodontic alternatives. Clear aligners consist of a series of removable plastic devices designed to reposition teeth to their optimal alignment. Pain is a common side effect of orthodontic treatment. It’s a primary factor contributing to patient discomfort, which can result in treatment delays and even the discontinuation of orthodontic care. Orthodontic forces applied to reposition teeth result in pain. Objectives: To assess the level of pain caused by the use of clear aligners in orthodontic treatments. Methods: The study design of this research is observational descriptive, using scoping review as an approach in accordance with PRISMA guidelines. An electronic database search was performed using PubMed and Google Scholar between February and May 2024. Results: There were six studies identified in the final synthesis. The pain intensity among all the studies is measured in relation to the pain caused by orthodontic appliances. Pain reaches its maximum within the initial 24 to 48 hours during initial stage, after device insertion and progressively diminishes between the 3rd and 7th day. Conclusion: the use of clear aligners results in mild pain intensity.